Effects of Basic Psychological Needs on Resilience: A Human Agency Model - Liu, Yuan; Huang, Xiaoxing (Frontiers in Psychology, 2021)
Academic resilience refers to the ability to recover and achieve high academic outcomes despite environmental adversity in the academic setting. At the same time, self-determination theory (SDT, Deci & Ryan, 1985, 2000) offers a human agency model to understand individuals’ autonomy to achieve in various fields. The present longitudinal study explored the factors influencing resilience from the analytical framework of SDT to investigate how basic psychological needs strengthen students’ resilience. A mediation model was proposed that resilience may mediate the relationship between basic psychological needs and academic performance. The results from 450 10th grade Chinese students showed that three basic psychological needs (i.e., autonomy, competence, and relatedness) facilitate academic resilience; academic resilience thus increases subsequent academic performance after controlling for previous test scores.